IMPLEMENTATION OF THE LESSON STUDY CYCLE IN PROJECT-BASED LEARNING TO ENHANCE DIGITAL LITERACY - Kemas Imron Rosadi; Meirisa Sahanata; Hedia Rizki; Fitri Kumala Dewi; Michrun Nisa Ramli (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
This study aims to describe the implementation of the Lesson Study for Learning Community (LSLC) cycle within Project-Based Learning (PjBL) and to analyze its impact on student engagement and digital literacy. The low level of students ability to utilize technology for academic purposes and for developing the competencies of prospective educators constitutes the primary background of this research.A descriptive qualitative method with a descriptive-analytic approach was employed. The research subjects were third-semester students of the Tadris Mathematics Study Program at State Islamic University Sulthan Thaha Saifuddin Jambi. Data were collected through questionnaires and digital observation sheets administered via Google Forms, and product assessment rubrics in the form of English-based mathematics E-Student Worksheets (ESW). Data analysis was conducted through the stages of data reduction, data display, and inductive conclusion drawing.The results indicate that the implementation of the PlanDoSee cycle within PjBL contributed positively to the learning process. The integration of digital technology, such as the use of the Canva platform in proposal preparation and project development, was proven effective in enhancing students digital literacy, particularly in searching for, evaluating, and critically creating digital learning content. Furthermore, collaboration within a learning community fostered reflective skills, critical thinking abilities, and teamwork in producing high-quality and relevant instructional products